(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The recently published Die vorrömische einheimische Toponymie des antiken Hispanien surveys various hypotheses regarding the pre-history of the place-name Τουκρίς and does not come to any definitive conclusion. If in fact it is Celtic in origins, there are several possibilities for its linguistic analysis. The paper tentatively suggest its derivation from PIE *teuh2- ‘to swell, be strong’, a prospect which has already been considered on the level of root etymology, and furnishes the analysis with a possible morphological elucidation. The toponym is perceived as a derivative in *-k- from this PIE root enlarged with *-r-, therefore (descriptively) *teuh2-k-r-. This pattern is found in other IE languages, while in Celtic (and elsewhere) enlargement in -n- from the same *teuh2-k- are well attested. The reference to the meaning of the PIE root also allows to deal with the semantics of the place-name, which is localised only roughly.